Assessment Instruments of Social Attitudes and Social Studies Learning Outcomes for Class V SD on Theme of Lingkungan Sekitar Kita - Yundarini, Ni Komang Suci; Nyoman Sudana, Dewa; Astawan, I Gede (Journal of Education Research and Evaluation, 2020)
The assessment instrument is an important component needed in the learning assessment process. However, in practice, there are still many teachers who have not been able to produce quality assessment instruments. The purpose of this study was to produce valid and reliable assessment instruments for social attitudes and social studies learning outcomes in class V on theme of lingkungan sekitar kita. In this study using a 4D development model, namely define, design, develop, disseminate. In this development research, it is only up to the development stage. The instrument used for the assessment of social attitudes was a questionnaire (questionnaire), while for the assessment of social studies learning outcomes used was a multiple-choice test. The data obtained would be analyzed the validity and reliability of each assessment instrument. The results of the analysis of the validity of the social attitude assessment instrument and social studies learning outcomes obtained an average value of 1, which means that the two assessment instruments have very high validity, while the results of the analysis of the reliability of the social attitude assessment instrument are 0,89 and the reliability of the social studies learning outcomes assessment instrument is 0,89. 0,85 which means that these two instruments have a high level of reliability. From these results, it can be concluded that the development of an assessment instrument for social attitudes and social studies learning outcomes is feasible to use in assessing students.